Analisis Pendekatan Struktural Pada Puisi “Tanah” Karya Wiji Thukul - Mochamad Fajar Fadillah; Muhamad Hazriel Triradiyana (Universitas Katolik Widya Karya Malang, 2023)
Poetry is the poet's interpretation of life. The interpretation reflects the poet's view of the surrounding reality. Reading poetry is a literary art enjoyment. Poetry is a rich literature that can be used to express oneself from the author, for example in Widji Thukul's poem entitled